The cultural values of architectural form in terms of current conditions of building technologies including prefabricated buildings - Radziewanowski, Zbigniew (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The present article concerns the problem of the contradiction between striving to maintain in the designed and implemented buildings of large volume in Polish area around the Tatras, in which it is justified to use current building technologies, including prefabricated buildings construction methods, and the need to continue the characteristic architectural forms of Tatra region. The demonstrated examples of architectural formation of buildings constructed during the interwar period-made for the needs of International Winter Olympics FIS, they used of the typical patterns of farms for the Alpine region. Such on example provides the evidence for the cultural pressure of a new function, i.e. skiing. Such an influence cannot be easily and consistently opposed in terms of logic performance of Tatra style current examples.